Unraveling the potential mechanisms of the anti-osteoporotic effects of the Achyranthes bidentata–Dipsacus asper herb pair: a network pharmacology and experimental study - Li, Tao; Li, Wenzhao; Guo, Xiaoning; Tan, Tingting; Xiang, Cheng; Ouyang, Zhengxiao (Frontiers in Pharmacology, 2023)
Osteoporosis is a prevalent bone metabolism disease characterized by a reduction in bone density, and leading to several complications that significantly affect patients' quality of life. The achyranthes bidentata-dipsacus asper (AB-DA) herb pair is commonly used in Traditional Chinese Medicine (TCM) for treating osteoporosis. This study aimed to investigate the therapeutic compounds and potential mechanisms of AB-DA using network pharmacology, molecular docking, molecular dynamics simulation, and experimental verification. Identified compounds of AB-DA were collected from TCMSP, TCM-ID, TCM@Taiwan, BATMAN databases, and relevant literature. Main bioactive ingredients were screened based on the criteria of "OB (Oral bioavailability) ≥30, DL (Drug-likeness) ≥0.18". Potential targets were predicted using PharmMapper and SwissTargetPrediction websites, while disease (osteoporosis) related targets were obtained from GeneCards, DisGeNET, and OMIM databases. The PPI network and KEGG/GO enrichment analysis were utilized for core targets and pathways screening in STRING and Metascape databases, respectively. A "drug-compound-target-pathway-disease" network was constructed in Cytoscape software to display core regulatory mechanisms. Molecular docking and dynamics simulation techniques explored the binding reliability and stability between core compounds and targets. In vitro and in vivo validation experiments were utilized to explored the anti-osteoporosis efficiency and mechanism of sitogluside. A total of 31 compounds with 83 potential targets for AB-DA against osteoporosis were obtained. The PPI analysis revealed several hub targets, including AKT1, CASP3, EGFR, IGF1, MAPK1, MAPK8, and MAPK14. GO/KEGG analysis indicated that the MAPK cascade (ERK/JNK/p38) is the main pathway involved in treating osteoporosis. The 'D-C-T-P-T' network demonstrated therapeutic compounds mainly consisting of iridoids, steroids, and flavonoids, such as sitogluside, loganic acid, and β-ecdysterone. Molecular docking and dynamics simulation analyses confirmed strong binding affinity and stability between core compounds and targets. Additionally, the validation experiments showed preliminary evidence of the antiosteoporosis effects. This study identified iridoids, steroids, and flavonoids as the main therapeutic compounds of AB-DA in treating osteoporosis. The underlying mechanisms may involve targeting core MAPK cascade (ERK/JNK/p38) targets, such as MAPK1, MAPK8, and MAPK14. In vivo experiments preliminarily validated the anti-osteoporosis effect of sitogluside. Further in-depth experimental studies are required to validate the therapeutic value of AB-DA for treating osteoporosis in clinical practice.